Answer:
volume= length × width × height
7×5×11
35×11
385cm³
Literal equations, simply put, are equations containing two or more variables. Your goal is to solve for just one variable with respect to others. If you know how to solve regular equations, then I guarantee you that solving literal equations will be a breeze.
The "heart" of literal equation is to isolate or keep by itself a certain variable on one side of the equation (either left or right) and the rest on the opposite side.
The exponential equation that can model the value of the camper van , in x years is y = 38000*(0.85)ˣ .
In the question ,
it is given that
the present value of the camper van (P₀) = $38000
given the depreciation rate is 15% each year (r)= -0.15
The future value y ,of the camper van can be given by the formula
y = P₀*(1 + r)ˣ
On putting the values , we get
y = 38000*( 1 - 0.15)ˣ
y = 38000*(0.85)ˣ
Therefore , The exponential equation that can model the value of the camper van , in x years is y = 38000*(0.85)ˣ .
Learn more about Exponential Equation here
brainly.com/question/22687491
#SPJ1
Answer:
-21
Step-by-step explanation:
We are told to find f(x) + g(x) for x= -3. Therefore, we must evaluate f(-3) and g(-3), then add them together.
First, evaluate f(-3).
f(x)=4x-7
To find f(-3), we need to substitute -3 in for x.
f(-3)= 4(-3)-7
Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition, Subtraction First, multiply 4 and -3.
f(-3)= -12-7
Next, subtract 7 from -12
f(-3)= -19
Next, find g(-3).
g(x)=2x+4
To find g(-3), substitute -3 in for x.
g(-3)= 2(-3)+4
Solve according to PEMDAS. First, multiply 2 and -3.
g(-3)= -6+4
Next, add -6 and 4
g(-3)= -2
Now, we can add f(-3) and g(-3) together.
f(-3) + g(-3)
f(-3)= -19
g(-3)= -2
-19 + -2
Add
-21
Answer:
9* 3 ^ (x-2)
Step-by-step explanation:
g(x) = 3^x
We know a^ (b) * a^(c) = a^ (b+c)
9* 3 ^ (x+2) = 3^2 * 3 ^(x+2) = 3^(2+x+2) = 3^x+4 not equal to 3^x
3*(9^(x+2)) = 3*3^2(x+2) = 3^1 * 3^(2x+4) =3^(2x+4+1) = 3^(2x+5) not equal
9* 3 ^ (x-2) = 3^2 * 3 ^(x-2) = 3^(2+x-2) = 3^x equal to 3^x
3*(9^(x-2)) = 3*3^2(x-2) = 3^1 * 3^(2x-4) =3^(2x-4+1) = 3^(2x-3) not equal